ATP2B2 de novo variants as a cause of variable neurodevelopmental disorders that feature dystonia, ataxia, intellectual disability, behavioral symptoms, and seizures - Poggio, Elena; Barazzuol, Lucia; Salmaso, Andrea; Milani, Celeste; Deligiannopoulou, Adamantia; Cazorla, Ángeles García; Jang, Se Song; Juliá-Palacios, Natalia; Keren, Boris; Kopajtich, Robert; Lynch, Sally Ann; Mignot, Cyril; et al. (Genetics in medicine, 2023)
PURPOSE: ATP2B2 encodes the variant-constrained plasma-membrane calcium-transporting ATPase-2, expressed in sensory ear cells and specialized neurons. ATP2B2/Atp2b2 variants were previously linked to isolated hearing loss in patients and neurodevelopmental deficits with ataxia in mice. We aimed to establish the association between ATP2B2 and human neurological disorders. METHODS: Multinational case recruitment, scrutiny of trio-based genomics data, in silico analyses, and functional variant characterization were performed. RESULTS: We assembled 7 individuals harboring rare, predicted deleterious heterozygous ATP2B2 variants. The alleles comprised 5 missense substitutions that affected evolutionarily conserved sites and 2 frameshift variants in the penultimate exon. For 6 variants, a de novo status was confirmed. Unlike described patients with hearing loss, the individuals displayed a spectrum of neurological abnormalities, ranging from ataxia with dystonic features to complex neurodevelopmental manifestations with intellectual disability, autism, and seizures. Two cases with recurrent amino-acid variation showed distinctive overlap with cerebellar atrophy-associated ataxia and epilepsy. In cell-based studies, all variants caused significant alterations in cytosolic calcium handling with both loss- and gain-of-function effects. CONCLUSION: Presentations in our series recapitulate key phenotypic aspects of Atp2b2-mouse models and underline the importance of precise calcium regulation for neurodevelopment and cerebellar function. Our study documents a role for ATP2B2 variants in causing heterogeneous neurodevelopmental and movement-disorder syndromes.
Keywords: Animals; dystonie; ATPasy přenášející vápník přes plazmatickou membránu; Phenotype; Seizures; Dystonia; lidé; Hearing Loss; Mice; vápník; myši; Intellectual Disability; Plasma Membrane Calcium-Transporting ATPases; neurovývojové poruchy; Behavioral Symptoms; Calcium; Cerebellar Ataxia; Neurodevelopmental Disorders; fenotyp; zvířata; cerebelární ataxie; mentální retardace; nedoslýchavost; záchvaty; behaviorální symptomy; Humans